Non-standard employment in Sweden - Research Institute of Industrial Economics, Stokholm; Skedinger, Per (Stockholm, 2018)
"In Sweden, as in many other countries, marginal groups tend to be overrepresented in non-standard employment. A decomposition of the employment rate of full-time workers on permanent contracts reveals that non-standard employment contributes to a substantially weaker labour market attachment for females and the foreign born than suggested by conventional employment figures alone.